O Orfanato Santo Eduardo e a assistência às crianças pobres em Uberaba – MG (1920 – 1964) - Souza, Marilsa Aparecida Alberto Assis (2018)
The present thesis is a result of a research in Education, line of research History and Historiography of Education, which was aimed at, as one of its main objectives, knowing how the public power, the religious entities and Uberaba society (MG) has dealt with the situation of poor children, some orphans and the abandoned, who would roamed around the streets of the city, whether loitering, begging or simply playing and practicing mischievous activities. The research was also aimed to investigate the genesis and the pathway of the institutions created to assist these children, especially Santo Eduardo Orphanage, created in 1920, still existing today. The time range established encompasses the 1920’s, from the year of its installation to 1964, when the policy of child assistance in Brazil acquires new unfoldings with the creation of Juvenile Welfare National Foundation - Fundação Nacional do Bem-Estar do Menor. The methodology employed established the dialectics among local context and national and state dimensions as to understand how the circulating speeches, legislations and national assistance policies for childhood care reverberated in the city of Uberaba, influencing the treatment offered to the children by local society. For that, several sources of research were used, such as newspapers, messages from the provincial presidents, legislations, iconographical records, guardianship and custody orders, institutions’ background, enrollment book, among others. The hypothesis that the charity and philanthropic actions of the society and religious entities of Uberaba driven to childhood did not have as the main concern life situation change of those individuals has been confirmed by the analysis of the sources that indicated that such actions were covered with a utilitarian and hygienist perspective. Regarding the religious institutions, whatever the belief professed, the opening of a new assistance institution was a way of such religion to gain legitimacy and demonstrate its power to society. As to institutions, the studies pointed out that they were mechanisms that allowed children’s and youngster’s isolation, whose pedagogy, oriented to moral regeneration, had as focus the preparation by work and for work. At the same time, these institutions were, for many of their users, a supportive refuge, where they could receive care that they would not have had if they were in the streets or with their families, besides having had the opportunity of accessing elementary education.